Unicorn thinks he's pretty great - Shea, Bob. (New York : Disney-Hyperion Books, 2013)
Envy turns to admiration and finally to friendship for Goat and Unicorn.
Keywords: Unicorns -- Fiction; Goats -- Fiction; Envy -- Fiction; Friendship -- Fiction; Unicorns -- Juvenile fiction; Goats -- Juvenile fiction; Envy -- Juvenile fiction; Friendship -- Juvenile fiction; Picture books for children